The The Effect of Types Planting Media and the Growth Regulatory Substances of Sprouts Extract on the Growth and Yield of Long Bean (Vigna unguiculata L.) - Ramadhanti, Choirul Lisa; Setiyono, Setiyono; Subroto, Gatot; Purnamasari, Ika; Patricia SM, Susan Barbara; Arum, Ayu Puspita; Savitri, Dyah Ayu (Newinera Publisher, 2024)
Long bean production in East Java has declined in the last three years because of the decreased soil fertility and the failure of pod formation. The addition of organic matter to the soil planting medium and spraying ZPT bean sprout extract are some efforts to increase the supply of nutrients and overcome flower fall. This study aimed to determine the interaction between the treatment of the planting media and ZPT of bean sprout extract toward growth and yield of long bean plants. The study was conducted factorially using a completely randomized design (CRD) in 3 replications. The first factor is the type of planting medium namely M0: soil; M1: soil+ compost; M2: soil+ chaff charcoal; M3: soil+ cocopeat. The second factor was the concentration of ZPT bean sprout extract, namely T0 control; T1: 10%; T2: 20%; T3: 30%. There was a very significant interaction between the treatment of the planting media and the bean sprout extract ZPT on the variable number of pods per plant and wet weight of pods per plant. The best treatment was the combination of the type of soil and compost growing media with ZPT bean sprout extract 20%. The main effect of the type of planting media treatment showed that the results were not significantly different for all observed variables. The ZPT treatment of bean sprout extract significantly affected the variables of flowering age, harvest age, and pod length per plant, the best treatment was the concentration of ZPT bean sprout extract 20%.